2023
DOI: 10.12688/wellcomeopenres.18650.1
|View full text |Cite
|
Sign up to set email alerts
|

Forgotten but not gone in rural South Africa: Urinary schistosomiasis and implications for chronic kidney disease screening in endemic countries

Abstract: Background: Urinary schistosomiasis caused by infection with Schistosoma haematobium (S. haematobium) remains endemic in Africa and is associated with haematuria and albuminuria/proteinuria. Kidney Disease Improving Global Outcomes clinical guidelines recommend evaluating proteinuria/albuminuria and glomerular filtration rate for chronic kidney disease (CKD) diagnosis. The guidelines are informed by population data outside of Africa but have been adopted in many African countries with little validation. Our st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Exposure to infectious diseases, such as schistosomiasis, tuberculosis, malaria, hepatitis B and C viruses represent an almost unique cluster of risk factors responsible for CKD in the African population 54,61,65 . In a more recent population‐based study in rural South Africa, schistosomiasis infection was associated with 8.7‐fold risk of CKD 66 . In a study from Tanzania, history of tuberculosis and schistosomiasis infection were, respectively, associated with an up to 3.8 and 2.5‐fold higher risk of CKD, accounting for 22% of the CKD burden 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to infectious diseases, such as schistosomiasis, tuberculosis, malaria, hepatitis B and C viruses represent an almost unique cluster of risk factors responsible for CKD in the African population 54,61,65 . In a more recent population‐based study in rural South Africa, schistosomiasis infection was associated with 8.7‐fold risk of CKD 66 . In a study from Tanzania, history of tuberculosis and schistosomiasis infection were, respectively, associated with an up to 3.8 and 2.5‐fold higher risk of CKD, accounting for 22% of the CKD burden 46 .…”
Section: Resultsmentioning
confidence: 99%
“…54,61,65 In a more recent population-based study in rural South Africa, schistosomiasis infection was associated with 8.7-fold risk of CKD. 66 In a study from Tanzania, history of tuberculosis and schistosomiasis infection were, respectively, associated with an up to 3.8 and 2.5-fold higher risk of CKD, accounting for 22% of the CKD burden. 46 A study from Zimbabwe also reported tuberculosis, history of schistosomiasis infection and malaria as the aetiological conditions of CKD patients.…”
Section: Ckd and Infectious Diseasesmentioning
confidence: 99%
“…Approximately 20-30 ml urine was collected from ARK study participants. Urine samples were processed and stored at -80°C prior to shipping to the Council for Scientific and Industrial Research laboratory for proteomic testing (30). Serum and urine creatinine was measured using an isotope dilution mass spectrometry traceable Jaffe method (31).…”
Section: Urine Collection and Measurement Of Egfr And Uacrmentioning
confidence: 99%
“…Urine samples were processed and stored at -80°C prior to shipping to the Council for Scientific and Industrial Research laboratory for proteomic testing (30). Serum and urine creatinine was measured using an isotope dilution mass spectrometry traceable Jaffe method (31). The 2009 Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) creatinine equation without adjustment for African American ethnicity was used to calculate eGFR (ml/min/1.73 m 2 ) (32).…”
Section: Urine Collection and Measurement Of Egfr And Uacrmentioning
confidence: 99%
See 1 more Smart Citation